A CASE STUDY ON HUMAN RIGHTS VS PRISONERS’ RIGHTS - Naidu, Nirnesh (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The balance between human rights and prisoners' rights has been a subject of intense debate within both national and international legal frameworks. While all individuals are guaranteed fundamental human rights, prisoners often face restrictions to their freedoms due to their confinement. This case study examines the intersection of these two rights, analyzing how prisoners’ rights are a subset of broader human rights and the extent to which prisoners should be entitled to rights while incarcerated. The study reviews international conventions, national constitutions, and landmark judicial rulings that address prisoners' rights, with particular focus on issues such as the right to life, freedom from torture, and access to healthcare. It also evaluates the challenges faced by prisoners in the context of legal, moral, and social perspectives. The aim is to identify potential gaps in legal frameworks and propose ways to ensure that prisoners' rights are upheld without compromising the principle of justice.